The New Employee Recruitment with the Spiderplot Method and Financial Management Calculation in Recruitment - Basory, Hartomy Akbar; Asepta, Uki Yonda; Kinanti, Elisa Agustina; Rossach, Michael Marshal Bintang; Prastiyo, Yuriko (Journal of Social Science, 2023)
This research aims to produce a new design of employee recruitment for the position of store head or pharmacist and the financial management calculation design in recruitment at the XYZ branch in Surabaya. The object of research is a profitable business venture in the pharmaceutical field and establishes the procurement and sale of pharmaceutical needs to the general public with national standards in Indonesia. The research tests used the employee selection system as well as the company's financial budget design for recruitment with qualitative research methods. The research was analyzed using the spider diagram method as well as B.E.S.S.T, Basory's - Economic - Suggestions for Solutions to the Trouble – method as well as simple financial statements of employee recruitment. Based on this research, the spider diagram method can be an alternative for evaluating potential new employees to get the best candidates. This research produces a scientific novelty regarding six indicators of new employee recruitment, namely salary, social network, experience, education, communication, and capital, as well as generating efficiency and effectiveness in simple financial statements related to employee recruitment.